Chromatic Bacteria – A Broad Host-Range Plasmid and Chromosomal Insertion Toolbox for Fluorescent Protein Expression in Bacteria - Schlechter, Rudolf O.; Jun, Hyunwoo; Bernach, Michał; Oso, Simisola; Boyd, Erica; Muñoz-Lintz, Dian A.; Dobson, Renwick C. J.; Remus, Daniela M.; Remus-Emsermann, Mitja N. P. (Frontiers in Microbiology, 2018)
Differential fluorescent labeling of bacteria has become instrumental for many aspects of microbiological research, such as the study of biofilm formation, bacterial individuality, evolution, and bacterial behavior in complex environments. We designed a variety of plasmids, each bearing one of eight unique, constitutively expressed fluorescent protein genes in conjunction with one of four different antibiotic resistance combinations. The fluorophores mTagBFP2, mTurquoise2, sGFP2, mClover3, sYFP2, mOrange2, mScarlet-I, and mCardinal, encoding for blue, cyan, green, green–yellow, yellow, orange, red, and far-red fluorescent proteins, respectively, were combined with selectable markers conferring tetracycline, gentamicin, kanamycin, and/or chloramphenicol resistance. These constructs were cloned into three different plasmid backbones: a broad host-range plasmid, a Tn5 transposon delivery plasmid, and a Tn7 transposon delivery plasmid. The utility of the plasmids and transposons was tested in bacteria from the phyla Actinobacteria, Proteobacteria, and Bacteroidetes. We were able to tag representatives from the phylum Proteobacteria at least via our Tn5 transposon delivery system. The present study enables labeling bacteria with a set of plasmids available to the community. One potential application of fluorescently-tagged bacterial species is the study of bacteria–bacteria, bacteria–host, and bacteria–environment interactions.